Institutions for Asian connectivity - Biswa Bhattacharyay (Asian Development Bank Institute (ADBI), 2010)
To make Asia more economically sustainable and resilient against external shocks, regional economies need to be rebalanced toward regional demand- and trade-driven growth through increased regional connectivity. The effectiveness of connectivity depends on the quality of hard and soft infrastructure. Of particular importance in terms of soft infrastructure which makes hard infrastructure work are the facilitating institutions that support connectivity through appropriate policies, reforms, systems, and procedures and through promoting effective coordination and cooperation. Asia has many overlapping subregional institutions involved in national and regional energy, transport, and telecommunications infrastructure connectivity. However, these institutions are characterized as being less effective, informal, and lacking a clear and binding system of rules and policies. This paper draws linkages between connectivity, growth and development, governance, and institutions. It details the benefits the region could achieve by addressing needed connectivity enhancements and the connectivity and financing challenges it faces. In addition, it presents various institutional options for regional infrastructure financing. To build seamless Asian connectivity, Asia needs an effective, formal, and rules-based institutional framework. The paper presents a new institutional framework together with the organizational structures of two new regional institutional mechanisms, namely the Pan-Asian Infrastructure Forum and the Asian Infrastructure Fund.
Keywords: R10; R40; R42; R48; R50; R51; R58; 330; Internationale Wirtschaftsbeziehungen; Wirtschaftswachstum; Institutionelle Infrastruktur; Internationale Wirtschaftsorganisation; Internationale wirtschaftspolitische Koordination; Asien